GANSO: New business model and technical assistance for the professionalization of sustainable livestock farming in the Colombian Orinoquia region - Ruden, Alejandro; Castro, Juan Pablo; Gutiérrez Solís, Jhon Freddy; Koenig, Simon; Sotelo, Mauricio E.; Arango, Jacobo (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This information note summarizes the state of livestock farming in the Orinoco region and the conditions that combine there to develop GANSO (abbreviation for sustainable livestock farming in Spanish, Ganaderia Sostenible), an innovative technical and financial assistance program aimed at a transformation to low-carbon and sustainable livestock farming that embraces productive, economic, social and environmental factors.